Eudesmane sesquiterpenes from Chinese liverwort are substrates of Cdrs and display antifungal activity by targeting Erg6 and Erg11 of Candida albicans. Issue 20 (15th October 2017) - Li, Siwen; Shi, Hongzhuo; Chang, Wenqiang; Li, Yi; Zhang, Ming; Qiao, Yanan; Lou, Hongxiang
Graphical abstract: Highlights: Twelve sesquiterpenes from Chinese liverwort T. quinquedentata were isolated. ent -iLL displayed antifungal activity through interfering with sterol synthesis. As a substrate of Cdrs, ent -iLL was retained intracellularly by Cdr inhibitors. Abstract: We isolated twelve sesquiterpenes from Chinese liverwort Tritomaria quinquedentata (Huds . ) Buch., including four new compounds. Among them, five eudesmane sesquiterpenes were ineffective against Candida albicans wild strain SC5314 but active towards efflux pumps-deficient strain DSY654 using Alamar blue assay. Further test of the most active agent of ent -isoalantolactone (8, ent -iLL) showed that it also inhibited the yeast-to-hyphal switch of DSY654 cells. The intracellular content measurement using high performance liquid chromatography (HPLC) revealed that ent -iLL was intracellularly accumulated in C. albicans when efflux pumps were deficient or inhibited by Cdrs inhibitor riccardin D, suggesting that the activity of ent -iLL was compromised by efflux pumps Cdrs. Moreover, ent -iLL potentially inhibited the activity of Erg11 and Erg6 of DSY654 and thereby resulted in the alteration of sterol composition by decreasing ergosterol contents and increasing zymosterol and lanosterol accumulation. Our study demonstrated that eudesmane sesquiterpenes, as the substrates of Cdrs, could interfere with sterol synthesis of C. albicans to exert antifungal activity when co-applied with Cdrs inhibitors.